A study of oleic acid oily base for the tropical delivery of dexamethasone microemulsion formulations - Bajpai, M; Sharma, P K; Mittal, A (Asian Journal of Pharmaceutics (AJP), 2014)
Dexamethasone Microemulsion systems composed of Water, oleic acid;Tween 80 and Isopropyl alcohol were investigated as potential drug delivery vehicles. Pseudo-ternary phase diagram was constructed at room temperature by titration, and the oil-to-surfactant/co-surfactant mass ratios (O/SC) that exhibit the maximum in the solubilization of water were found. Microemulsion formulations were evaluated for pseudo ternary phase study, Globule size, thermal stability, centrifugation stress testing, specific gravity, pH study, in vitro release on rat abdominal skin.The permeation data showed that microemulsion formulations increased dexamethasone flux 200–400 fold over the control, but permeability coefficients were decreased by 4 times.The superior transdermal flux of dexamethasone was due to 1000 fold improvement in solubilization of dexamethasone by microemulsions using lecithin. It can be concluded from the study that the dexamethasone microemulsions can be potentially used for improved topical drug delivery.